8‐O‐Acetyl Shanzhiside Methylester Attenuates Cerebral Ischaemia/Reperfusion Injury through an Anti‐Inflammatory Mechanism in Diabetic Rats. (10th June 2014) - Zhang, Liang; Kan, Ze‐Chun; Zhang, Xiu‐Li; Fang, Han; Jiang, Wang‐Lin
Abstract Inflammatory activation plays a vital role in the pathophysiological mechanisms of stroke and diabetes mellitus (DM), exerts the deleterious effects on the progression of the brain and leads to vascular damage in diabetic stroke. The objectives of this study were to investigate the effects of 8‐O‐acetyl shanzhiside methylester (ND01) on tumour necrosis factor‐α (TNF‐α)‐stimulated SH‐SY5Y cell line in vitro and the experimental ischaemic diabetic stroke model in vivo. TNF‐α‐stimulated SH‐SY5Y cells were pre‐incubated with ND01, then analysed protein expression. For in vivo experiment, the diabetic rats were subjected to middle cerebral artery occlusion (MCAO) for 30 min. followed by reperfusion for 23 hr. Treatment of SH‐SY5Y cells with ND01 blocked TNF‐α‐induced nuclear transcription factor κB (NF‐κB) activation and decreased high‐mobility group box‐1 (HMGB‐1) expression. ND01 40 mg/kg demonstrated significant neuroprotective effect even after delayed administration at 4 hr after I/R. ND01 40 mg/kg attenuated the histopathological damage, decreased brain swelling, inhibited NF‐κB activation and reduced HMGB‐1 expression in ischaemic brain tissue. These data show that ND01 protects diabetic brain against I/R injury with a favourable therapeutic time‐window by alleviating diabetic cerebral I/R injury and attenuating blood–brain barrier (BBB) breakdown, and its protective effects may involve HMGB‐1 and NF‐κB signalling pathway.